ISOLASI SENYAWA AKTIF ANTIOKSIDAN RIMPANG GANDASULI (HEDYCHIUM CORONARIUM) - Suhardiman, Aris (Journal of Pharmacopolium, 2018)
Antioxidants are compounds that can inhibit the formation of free radicals and protect the body from various degenerative diseases and cancer. One of the plants of Zingiberaceae tribe that could potentially be an antioxidant is Hedychium coronarium. This plant grows in several countries in Asia and Africa, has been widely used to treat various diseases. This study aims to isolate the antioxidant active compound from Hedychium coronarium. The sample was extracted by maseration using 96% ethanol. The fractionation was carried out by liquid-liquid extraction using n-hexane and ethyl acetate. The fractionation fraction of ethyl acetate continued with vacuum liquid chromatography (VLC) method. Purification by preparative thin layer chromatography. Purity test was done with single development with three different eluents and two dimensional thin layer chromatography. Identification of isolate using UV-Vis and infrared spectrophotometry. Testing of antioxidant activity of isolate was done qualitatively using DPPH free radical reduction method. Pure isolates were obtained from the fraction number 6 of VLC yields and has antioxidant activity with yellow spot after being sprayed with 0.2% DPPH in metanol. The isolate has a maximum wavelength of 262 nm and 270 nm and the isolate contains O-H, C-H, and C=C groups.